Management’s Perception of Succession Planning Towards Crafting a Succession Plan: The Case of a Higher Education Institution in Batangas - Calinao-De Guzman, Twinkle M (Archives of Business Research, 2024)
People are an organization’s most valuable resource; hence one must employ strategies that would increase these assets. While it is understood that these assets provide the organization’s competitive advantage, not much of their value is acknowledged. This study explored the management’s perception of succession planning as input for creating a succession plan. Specifically, this study determined the management’s perception in terms of the value and process of succession planning, its alignment with organizational culture, identified the resource needs to be considered, determined significant challenges to the effective implementation of a succession plan, and integrated data as inputs for the creation of succession plan. Qualitative research, specifically a case study, was utilized since the scope was limited to a specific organization. The nine management employees of the identified HEI were the study’s participants. Key informant interviews and documentary analysis were used in data gathering while triangulation was carried out to verify the credibility of results. Findings revealed that although management employees perceived succession planning as advantageous, they only had slight awareness of it. Cultural variables in management, resources, and systems generally impede the creation and implementation of a succession plan rather than support it. Further, the required KSAs of the identified talent pipeline and budgetary resources were significant considerations. Employee turnover, resource constraints, and the “padrino” system posed challenges to the effective implementation of a succession plan. Lastly, the analysis resulted in a crafted succession plan with the integration of a professional development plan spanning five years.